The GALAH survey: effective temperature calibration from the InfraRed Flux Method in the Gaia system. Issue 2 (10th August 2021) - Casagrande, Luca; Lin, Jane; Rains, Adam D; Liu, Fan; Buder, Sven; Horner, Jonathan; Asplund, Martin; Lewis, Geraint F; Martell, Sarah L; Nordlander, Thomas; Stello, Dennis; Ting, Yuan-Sen; et al.
ABSTRACT: In order to accurately determine stellar properties, knowledge of the effective temperature of stars is vital. We implement Gaia and 2MASS photometry in the InfraRed Flux Method and apply it to over 360 000 stars across different evolutionary stages in the GALAH DR3 survey. We derive colour-effective temperature relations that take into account the effect of metallicity and surface gravity over the range 4000 KT_eff8000 K, from very metal-poor stars to supersolar metallicities. The internal uncertainty of these calibrations is of order 40–80 K depending on the colour combination used. Comparison against solar-twins, Gaia benchmark stars, and the latest interferometric measurements validates the precision and accuracy of these calibrations from F to early M spectral types. We assess the impact of various sources of uncertainties, including the assumed extinction law, and provide guidelines to use our relations. Robust solar colours are also derived.